Navigation problems of ICSI or naive blastocyst can be solved with artificial blastocyst - Celik, Onder; Acet, Mustafa; Arpaci, Haldun; Dikbas, Levent; Imren, Aytac; Duran, Bulent; Aydin, Suleyman (Biomed Central Ltd, 2018)
Embryos have evolved a remarkable capacity to find implantation site. The impressive navigation ability of natural blastocysts may rely on highly sensitive signals arising from embryos and specialized signal processing strategies in the endometrium. Navigation capabilities may be compromised in ICSI embryos because of altered biochemical signaling. The design and delivery of artificial blastocyst (AB) carrying strong chemical signals may allow ICSI embryos to more easily locate to and be retained in the implantation zone. ICSI embryos will attach easily to the implantation zone after it is found by the AB. Co-transfer of the AB together with the ICSI embryo may overcome potential difficulties in implantation due to impaired embryo-maternal communication in cases with implantation failure.
Keywords: Embryo Implantation; Endometrium; Mechanisms; Expression; Decline; Uterus